Epidemiology of burns in the state of Minas Gerais. What has changed in a decade? - Rodrigo Pimenta Sizenando; Higner Luis Costa Forastieri; Guilherme Neves Furtado; Morgana Pinto Motta Roque; Kelly Danielle Araújo; Ana Paola Reis Fagundes Santos (Revista Brasileira de Cirurgia Plástica)
Introduction: With a major impact on the population, burns require epidemiological analysis and constant planning for the prevention, treatment, and rehabilitation of patients. This work aims to compare, after a decade, the indicators of the Burn Treatment Center at Hospital João XXIII, in Belo Horizonte, MG, covered in the article “Epidemiology of burns in the state of Minas Gerais”, published in the Revista Brasileira de Cirurgia Plástica with data from 2010, to validate current and future strategies. Method: Review of the medical records of patients suffering from burns, admitted to the aforementioned center in 2020. Results: 473 burn victims were hospitalized during the period, 87.5% were caused by an accident, 34.5% due to hot liquids, 23.7% by alcohol; 61.9% from the interior of the state of Minas Gerais; and 63.4% were male. The average age was 30 years, the average burned body surface area was 18.8% and the average length of stay was 25 days. 580 surgical debridement and 473 autologous skin grafts were performed. 7.4% of patients died, corresponding to 29.5% of those admitted to the adult ICU, with an average burned body surface area of 49.7%, and 10.5% of those admitted to the pediatric ICU. The biggest cause of death was sepsis, in 57.1% of cases. Mortality decreased from 16.3% to 7.4% in the period studied. Conclusion: The profile of patients hospitalized for burns remained largely the same after 10 years. There was an increase in the number of visits to burn victims in the interior of the state and burns caused by hot liquids became more frequent than those caused by alcohol. “The search for compliance with treatment based on world literature resulted in reduction in mortality.”